2018
DOI: 10.21577/1984-6835.20180009
|View full text |Cite
|
Sign up to set email alerts
|

Antinociceptive and Anti-inflammatory Activities of the Ethanolic Extract, of Fractions and of Epicatechin Isolated from the Stem Bark of Ximenia americana L. (Oleacaceae)

Abstract: Resumo:As ações antinociceptivas e anti-inflamatórias do extrato etanólico, das frações e da epicatequina (XM-Catequina) isolada a partir dos extratos etanólicos das cascas de Ximenia americana L. foram determinadas utilizando modelos in vivo como contorções induzidas pelo ácido acético, teste de formalina, teste de placa quente, peritonite induzida por zimosan e ensaio in vitro de inibição da ciclo-oxigenase. O teste de contorção revelou efeitos inibitórios maiores que 90% do extrato etanólico, das frações e … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
3
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 13 publications
2
3
0
1
Order By: Relevance
“…This efficacy was observed between all doses of the combinations and those of the extracts alone. Anti-inflammatory effect of the extract of Ximenia americana and Terminalia macroptera has been previously demonstrated by other authors, 13,25 which corroborates the results of this study.…”
Section: Discussionsupporting
confidence: 93%
“…This efficacy was observed between all doses of the combinations and those of the extracts alone. Anti-inflammatory effect of the extract of Ximenia americana and Terminalia macroptera has been previously demonstrated by other authors, 13,25 which corroborates the results of this study.…”
Section: Discussionsupporting
confidence: 93%
“…However, these extracts remained significantly less effective than the reference drug (Celecoxib, IC 50 = 2.96 ± 0.81, p < 0.05, p < 0.001, p < 0.001 respectively for X. americana, T. macroptera and S. senegalensis) All other extracts were largely less effective that the reference drug celecoxib (p < 0.0001) (Figure 2). These results are in accordance with previousreport from Dias et al (2018) who found that catechin from X. americana significantly inhibited COX-1 and COX-2, providing evidence that flavonoids elicit antiinflammatory activity. Furthermore, other studies have shown that the hydroethanolic extracts of X. americana, T. macroptera and S. senegalensis contain high levels of polyphenols and flavonoids (Ballo et al, 2021), suggesting that the present characterized inhibitory effects of the selected plant extracts on COX-1 and COX-2 are therefore probably due to the presence of secondary metabolites such as flavonoids and polyphenols in general, contained in significant levels in these extracts.…”
Section: Cyclooxygenase (Cox-1 and Cox-2) Inhibitory Activitysupporting
confidence: 93%
“…Antimicrobial and antiviral (showed inhibition against Herpes simplex virus type 1 (HSV-1) (Musarra-Pizzo et al, 2019) Anti-oxidant, antitumor, antibacterial, antifungal, antidiabetic, anti-inflammatory, antiproliferative and antitumor (Cosarcã et al, 2019) Antioxidant, UV protective, anti-allergenic, anti-inflammatory, anti-microbial, anti-viral and anti-cancer (Bae et al, 2020) Antiviral (showed inhibition against pandemic influenza A (H1N1) (You et al, 2018) Epicatechin Antiviral (showed inhibitory effect against Mayaro (MAYV) virus and other alphavirus viruses (Ferreira et al, 2018) Antinociceptive and anti-inflammatory (Dias et al, 2018) Antibacterial (Ezhil and Lakshmi, 2017) Antidiabetic (Ibrahim et al, 2018) Anti-infective (Song, 2017) Anti-oxidant, antimicrobial, anti-inflammatory, antitumor, antidiabetic, anticancer and cardioprotective (Prakash et al, 2019) Antioxidant and anticollagenase (showed a high inhibitory power against the collagenase enzyme, responsible for the degradation of matrix collagen and the photo-aging process. (Geeta et al, 2019) UV protection (Prasanth et al, 2020)…”
Section: Catechinmentioning
confidence: 99%